2003
DOI: 10.1109/ted.2003.812484
|View full text |Cite
|
Sign up to set email alerts
|

Auger recombination-enhanced hot carrier degradation in nMOSFETs with a forward substrate bias

Abstract: Enhanced hot carrier degradation in nMOSFETs with a forward substrate bias is observed. The degradation cannot be explained by conventional channel hot electron effects. Instead, an Auger recombination-assisted hot electron process is proposed. In the process, holes are injected from the forwardbiased substrate and provide for Auger recombination with electrons in the channel, thus substantially increasing channel hot electron energy. Measured hot electron gate current and the light emission spectrum provide e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…Interestingly, similar hot-carrier-driven interface trap generation has also been seen under simultaneous low-voltage and highcurrent stress conditions, where electric fields are not large enough to produce hot carriers. Some studies have suggested Auger generation as a candidate mechanism for hot-carrier generation under such stress conditions [3]- [6], and in [7], we provided evidence to support Auger generation as the driving mechanism. This paper expands on that previous study ( [7]) through the explanation of the role Auger recombination plays in hot-carrier degradation, comparison of the effects of mixedmode stress with high-current stress, and explanation for the different behaviors attributed to the Auger recombination seen in high-current stress using stress measurement data and calibrated TCAD simulations.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…Interestingly, similar hot-carrier-driven interface trap generation has also been seen under simultaneous low-voltage and highcurrent stress conditions, where electric fields are not large enough to produce hot carriers. Some studies have suggested Auger generation as a candidate mechanism for hot-carrier generation under such stress conditions [3]- [6], and in [7], we provided evidence to support Auger generation as the driving mechanism. This paper expands on that previous study ( [7]) through the explanation of the role Auger recombination plays in hot-carrier degradation, comparison of the effects of mixedmode stress with high-current stress, and explanation for the different behaviors attributed to the Auger recombination seen in high-current stress using stress measurement data and calibrated TCAD simulations.…”
Section: Introductionsupporting
confidence: 72%
“…Studies of hot-carrier injection in MOSFETs have shown that Auger recombination and the similar electron-electron scattering process can contribute to hot-carrier degradation under certain conditions [6], [14]. Though it has reduced the probability of creating hot carriers with sufficient energy, the Auger generation degradation process is enhanced relative to mixed-mode degradation due to the physical location where these processes occur within the device.…”
Section: Hot-carrier Physicsmentioning
confidence: 99%
“…In particular, opposite channel injection phenomena may occur [7], and, with the reduction in film thickness and fully depleted (FD) operation, coupling effects between the damage generated at the different gates [1]. More recently, with the introduction of very thin (below around 2.5 nm) SiO 2 -based gate oxides, the high gate bias regimes have been shown to suffer from enhanced HCD [8,9], what has been attributed to the impact of the EVB direct tunneling injection phenomena, where the majority carriers introduced into the floating film have been reported to be responsible for this enhanced HCD [10].…”
Section: Introductionmentioning
confidence: 99%
“…Superior performance is obtained because the twodimensional electrons (2DEG) are confined in In y Ga 1−y As QW with high mobility and saturation velocity [14,15]. On the other hand, AlGaAs-based hydrogen sensors are alternative candidates for their good performance of high detection sensitivity, fast response and widespread regimes of operating temperature and hydrogen concentration [16]. In this work, an interesting GaAs PHEMT-type hydrogen sensor with a Pd/Al 0.24 Ga 0.76 As metal-semiconductor Schottky contact structure is fabricated and studied.…”
Section: Introductionmentioning
confidence: 99%